2019
DOI: 10.1037/drm0000102
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between video game play factors and frequency of lucid and control dreaming experiences.

Abstract: Lucid and control dream states have been linked to a variety of positive psychological outcomes, but are uncommon and difficult to induce. Delineating connections between lucid and control dreaming and immersion in other virtual environments could aid in understanding the nature of those dream states and developing more effective induction training. Video game play takes place in immersive virtual environments and has been linked to more frequent lucid dreaming (Gackenbach, 2006(Gackenbach, , 2009. The current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It is also possible that Reddit contains a larger proportion of gamers than other social media platforms. It has been suggested that lucid dreaming and specifically dream control increase with video game use [ 76 , 77 ] (though see [ 78 ]), and if r/LucidDreaming follows this trend it might have influenced our theme totals (e.g. inflating dream enhancement and deflating lucid dysphoria).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that Reddit contains a larger proportion of gamers than other social media platforms. It has been suggested that lucid dreaming and specifically dream control increase with video game use [ 76 , 77 ] (though see [ 78 ]), and if r/LucidDreaming follows this trend it might have influenced our theme totals (e.g. inflating dream enhancement and deflating lucid dysphoria).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of classifications, there exists significant variation across studies. For instance, while several use the Schredl and Erlacher (2004) conceptualization (e.g., Denis and Poerio, 2017), others employ different wording (e.g., Sestir et al, 2019), or have devised alternative measures (Aviram and Soffer-Dudek, 2018; the Frequency and Intensity Lucid Dream questionnaire, FILD).…”
Section: Discussionmentioning
confidence: 99%
“…Lucid dreaming and mindfulness training could be utilized in a pre/post training design or randomized control trials using in-person or smartphone-based meditations, which have become widely used both in research and among the general public. Further, a recent study by Sestir et al (2019) demonstrated that video gaming can increase lucid dreaming, and therefore intervention studies that employ both mindfulness training and video games geared toward lucid dreaming abilities could be piloted. A potential dreaming intervention that utilizes both video gaming and mindfulness has the ability to be beneficial in increasing the frequency of lucid dreaming and dream control occurrences.…”
Section: Limitations and Future Researchmentioning
confidence: 99%